The Endemic Stage of COVID-19: Mental Health and Wellbeing Among University Students - Clark, Mitchell (2025)
This study was intended to examine a range of independent/predictor variables that may impact the independent/outcome variables of stress, anxiety, depression, and wellbeing. The predictor variables examined in this study are workload, loneliness, social support, physical health, compassion, financial stress, sense of meaning in life, and substance use. This study employed a correlational design and was conducted at Mount Royal University during Fall 2022 and Winter 2023. Survey ratings were collected from 384 students from the participant pool of students taking an introductory psychology course. Participants completed a range of surveys measuring stress, anxiety, depression, and wellbeing, as well as being examined in this study are workload, loneliness, social support, physical health, compassion, financial stress, sense of meaning in life, and substance use. Two correlation analyses were conducted between the variables. The study revealed several significant correlations between psychological constructs and well-being indicators. This study contributes valuable insights into the factors influencing mental health and well-being in a post-pandemic/endemic world. Future research could explore these relationships and develop targeted interventions to improve mental health outcomes in vulnerable populations.